Promoting Digital Competencies in Pre-Service Teachers: The Impact of Integrative Learning Opportunities - Köstler, Verena; Wolff, Monika-Sybille (Education sciences, 2025)
Offering learning opportunities for developing digital competencies in pre-service teacher education remains challenging despite its growing importance in preparing future educators. This study investigates the effectiveness of integrative learning opportunities, called “digitally enhanced courses”, which combine subject-specific and digital learning objectives. Implemented at a German university (2019–2023). These courses aimed to promote digital competencies required for technology-supported teaching. Using survey data from 312 pre-service teachers, the research examined students’ self-assessed digital competencies, technology acceptance, and value–cost assessments through multiple measurement instruments, including TPACK scales, the Technology Acceptance Model, and Expectancy–Value beliefs. Results revealed significantly higher self-assessed digital competencies in private contexts compared to teaching situations. While mere course participation showed no significant impact, both the frequency and number of attended courses positively correlated with higher self-assessed digital skills across all TPACK dimensions. Additionally, increased technology acceptance and higher success expectations were associated with enhanced teaching-related digital competencies. The findings emphasize that the effectiveness of digitally enhanced courses is contingent upon systematic implementation and student engagement, highlighting the need for structured curricular integration of digital competency development in teacher education through comprehensive, spiral-curriculum approaches rather than isolated interventions. However, this study’s reliance on self-reported data may introduce social desirability and subjective estimation bias, and its cross-sectional design limits causal interpretations. Future research should employ longitudinal approaches to examine competency development over time, incorporate objective performance-based assessments, and explore how instructional design and curricular integration influence digital competency acquisition.